PENGARUH PENGGUNAAN MODEL PICTURE AND PICTURE TERHADAP KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELASVII SMP NEGERI 6 PARIAMAN Nurul Ikrima, Indriani Nisja, Lira Hayu Afdetis Mana Program Studi Pendidikan Bahasa dan Sastra Indonesia STKIP PGRI Sumatera Bar - nurul ikrima (Horizon, 2021)
ABSTRACTThe study is set against the background of such problems as the following. Students are less interested in taking lessons. Students have not been able to write the textbook procedure according to the correct writing criteria. The study aims to describe the ability to write text of student procedure before and after using the picture and picture model and the effect the use of the picture and picture model on the ability to write the text of class procedure VII SMP N 6 Pariaman. This type of research is quantitative using experimental methods. The sample in this study were 25 students of class VII. The data in this study is the score of textual ability before using the picture and picture and text capability score of procedure after using the picture and picture class model VII SMP N 6 Pariaman. Based on research results may be summarized as follows. First, the ability to write the text procedure class VII SMP N 6 Pariaman before using a picture and picture model achieves an average of 66,85 with a qualification of more than Enough (LdC). Second, the students' ability to write procedural texts of class VII SMP N 6 Pariaman after using the Picture and Picture model obtained an average score of 76.18 with good qualifications (B). Third, based on the t-test, it is obtained tcount = 3.93> t table = 1.71. The test criteria for t is accepted, t count> t table, in other words H1 is accepted and H0 is rejected. Thus, the use of the Picture and Picture model has an effect on the ability to write the text of class procedure VII SMP N 6 Pariaman. Keywords:Writing, Procedure Text, Picture and Picture.